PERILAKU KONSUMEN KERIPIK NENAS PRODUKSI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR - Ningrum, Edni Astrina Widya; Yulida, Roza; Yusri, Jum'atri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study is describe the perceptions, attitudes and preferences consumers of pineapple chips Kualu Nenas village production Tambang district kampar district. This study was conducted in Pekanbaru city, which started from June 2016 until January 2018 with the number of respondents as much as 120 respondents. Data were analyzed skala likert. The results concluded that: perceptions, attitudes and preferences are sufficient to influence the consumers of pineapple chips Kualu Nenas village production Tambang district kampar district.Keywords: pineapple chips, consumer, influence